Front Cover: Optical‐Mode Structure of Micropillar Microcavities Containing a Fluorescent Conjugated Polymer (Adv. Quantum Technol. 2/2020). Issue 2 (13th February 2020) - Al‐Jashaam, Faleh L.; Jayaprakash, Rahul; Coles, David M.; Musser, Andrew J.; Georgiou, Kyriacos; Lidzey, David G.
Abstract : Researchers from the University of Sheffield use focused‐ion beam lithography to etch micropillars into a planar microcavity formed from two dielectric mirrors placed on either side of a fluorescent conjugated‐polymer (see article number 1900067 by David G. Lidzey and co‐workers). The photoluminescence from the micropillars is explored using a series of advanced imaging techniques. It is shown that micropillar emission is quantized into a series of modes arising from vertical and lateral confinement within the pillar, with a model used to describe the energy and spatial distribution of the various optical modes.